Kontribusi Peradaban Andalusia terhadap Barat dan Kontekstualisasi Bagi Pendidikan Islam Masa Kini - Yazida Ichsan (At-Taqaddum, 2020)
The history of civilization during classical Islam experienced significant developments, especially during the Andalusian society. This article aims to describe the Andalusian civilization's glories and its contribution to the renaissance and Aufklarung's birth in the West and its contextualization to advance Islamic education today. This article is a literature research concerning historical literature sources. This study uses a heuristic approach, criticism, interpretation and histography. The analysis and discussion results show that Andalusia has several forms of progress that Western impact progress, which includes several things. First, a civilization which is manifested in thoughts works of art, buildings and literature. Second, education adopted by Western nations through students. Third, a translation which revives the awareness of the use of ratio. As for the current educational context, the Andalusia civilization's implications contribute to an understanding of scientific reasoning, integrating qauliyyah, kauniyah and nafsiyyah logic by forming a learning climate being open to learning Western science without leaving the spiritual element in Islam.